Synthesis and Evaluation of Biological Activities of Bis(spiropyrazolone)cyclopropanes: A Potential Application against Leishmaniasis - Olalla Barreiro-Costa; Gabriela Morales-Noboa; Patricio Rojas-Silva; Eliana Lara-Barba; Javier Santamaría-Aguirre; Natalia Bailón-Moscoso; Juan Carlos Romero-Benavides; Ana Herrera; Cristina Cueva; Lenin Ron-Garrido; Ana Poveda; HEREDIA MOYA, JORGE HUMBERTO (MDPI AG, 2021)
This work focuses on the search and development of drugs that may become new alternatives to the commercial drugs currently available for treatment of leishmaniasis. We have designed and synthesized 12 derivatives of bis(spiropyrazolone)cyclopropanes. We then characterized their potential application in therapeutic use. For this, the in vitro biological activities against three eukaryotic models—S. cerevisiae, five cancer cell lines, and the parasite L. mexicana—were evaluated. In addition, cytotoxicity against non-cancerous mammalian cells has been evaluated and other properties of interest have been characterized, such as genotoxicity, antioxidant properties and, in silico predictive adsorption, distribution, metabolism, and excretion (ADME). The results that we present here represent a first screening, indicating two derivatives of bis(spiropyrazolone)cyclopropanes as good candidates for the treatment of leishmaniasis. They have good specificity against parasites with respect to mammalian cells.